Towards a (r)evolutionary M.E.Ch.A: intersectionality, diversity, and the queering of Xicanism@ - Baca Huerta, Sandra Yesenia (Kansas State University, 2013)
This thesis examines Movimiento Estudiantil Chicano de Aztlán (M.E.Ch.A), one of the oldest organizations of the Chicano movement. History shows that M.E.Ch.A has been able to reflect on itself and change accordingly; thus, it has been able to stay alive due to internal debates from the 1960s to the 1990s. In the 1960s, male, heterosexual Mexicans dominated the Chicano movement. In the 1980s, Xicanas challenged them to look past their privileges into more intersectional, inclusive identities. My research question is: in 2013, how do Californian MEChistAs view themselves, their political consciousness, and their social justice work? MEChistAs view themselves as an inclusive, diverse, and progressive organization. Chican@/Xican@ is a political identity and ideology that includes women, queers, and non-Mexicans. Women and queers took leadership of the organization, which shows that the revised historical documents made a difference. However, M.E.Ch.A continues a Mexican-centric organization that isolates Central Americans, South Americans, and Afro-Latin@s. M.E.Ch.A has changed since the 1960s in many ways, but the work continues. M.E.Ch.A still needs to address several internal debates as an organization, such as: Aztlán’s meanings, community versus campus organizing, generational gaps, and working with social organizations. Despite these debates, M.E.Ch.A has survived. Using 22 in-depth interviews with contemporary MEChistAs in California from 10 different universities, I examined the identities and politics of M.E.Ch.A activists. I enact Dorothy Smith and Patricia Hill Collin’s standpoint theory to guide the research and apply third world feminism and ideology/utopia theories to analyze the ideas and concepts of the MEChistAs.
Keywords: Social movement; Chicano/a movement; Student activism; Intersectionality; Xicanisma/o; Movimiento Estudiantil Chicano de Aztlán (M.E.Ch.A); Sociology (0626)